CLINICAL ASSESSMENT OF EXPERIMENTALLY INDUCED OSTEOARTHRITIS RAT MODEL IN RELATION TO TIME - H. M. Khan; M. Ashraf; A. S. Hashmi; M. U. D. Ahmad; A. A. Anjum (Journal of Animal and Plant Sciences, 2012)
Osteoarthritis (OA) is an age related joint disease manifested by progressive degeneration of articular cartilage and is associated with chronic pain. Dynamics of pain, lameness and swelling during developmental stages of experimentally induced OA in rat model. OA was induced in twenty five male Wistar rats by injecting papain (10mg/0.5cc buffer solution) intra-articularly and 0.9 per cent sterile saline solution in another group (n=5) of rats served as control. Clinical assessment based on pain, lameness and swelling was done on control group (day 0) and OA groups (n = 5) on 1st, 7th, 14th, 21st and 28th days post papain injection. Pain was recorded by hot water tail flick assay, degree of lameness by ordinal scoring system and swelling measured by calibrated digital caliper. Observations of OA groups were compared with of control group. Highest statistical mean retention time (3.43±.44) was observed on day 21st post papain injection, followed by day 14th (2.80±.59), 28th (2.46±.14), 7th (1.95±.47) and 1st (1.89±.47). Highest clinical score for swelling among osteoarthritis groups was determined on day one (6.31±.54), followed by day 07 (2.56±.28), 14 (2.30±.09), 21 (1.45±1.01) and 28 (1.14±.39), respectively. Highest lameness score was observed on 1st (2.40±0.55) and 14th day (2.40±0.55) followed by 21st day (2.20 ± 0.84), 7th day (1.60±.55). The least lameness score was observed on 28th day i.e. 1.40±.55. Highest cumulative mean clinical score observed was 10.38±1.10 (1st day) followed by 7.70±1.14 (14th day), 7.06±1.28 (21st day), 6.11±0.80 (7th day) and 5.00±0.34 (28th day) post papain injection. Clinical score was zero in control group. It was concluded that inflammatory signs of pain, lameness and swelling were reduced with passage of time in OA groups. This model may be used to study the efficacy of symptomatic slow acting/structure modifying drugs in pain management.
Keywords: Osteoarthritis; papain; pain; lameness and swelling.